La construction du sens social en discours. Le cas de Grexit - Biardzka, Elżbieta (Studia Romanica Posnaniensia, 2017)
In this paper we analyse occurrences of the word Grexit in terms of syntagmatic and textual relations. We aim to show the semantic and pragma-discursive determinations of its social meaning, which appears to be vague and confounding. The study is based on the corpus of press texts published in Le Monde, Libération and Le Figaro between 6 July 2015 (the day after the Greek referendum) and 11 July 2015 (date of the agreement between Greece and its creditors).